Comparing Cone Structure and Function in RHO- and RPGR-Associated Retinitis Pigmentosa - Foote, Katharina G. (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To study cone structure and function in patients with retinitis pigmentosa (RP) owing to mutations in rhodopsin (RHO), expressed in rod outer segments, and mutations in the RP-GTPase regulator (RPGR) gene, expressed in the connecting cilium of rods and cones. METHODS: Four eyes of 4 patients with RHO mutations, 5 eyes of 5 patients with RPGR mutations, and 4 eyes of 4 normal subjects were studied. Cone structure was studied with confocal and split-detector adaptive optics scanning laser ophthalmoscopy (AOSLO) and spectral-domain optical coherence tomography. Retinal function was measured using a 543-nm AOSLO-mediated adaptive optics microperimetry (AOMP) stimulus. The ratio of sensitivity to cone density was compared between groups using the Wilcoxon rank-sum test. RESULTS: AOMP sensitivity/cone density in patients with RPGR mutations was significantly lower than normal (P < 0.001) and lower than patients with RHO mutations (P < 0.015), whereas patients with RHO mutations were similar to normal (P > 0.9). CONCLUSIONS: Retinal sensitivity/cone density was lower in patients with RPGR mutations than normal and lower than patients with RHO mutations, perhaps because cones express RPGR and degenerate primarily, whereas cones in eyes with RHO mutations die secondary to rod degeneration. High-resolution microperimetry can reveal differences in cone degeneration in patients with different forms of RP.